Book Reviews - Susskind, Jacob L.; Fischer, Robert; Luehrs, Robert B.; McCarthy, Joseph M.; Micciche, Pasquale E.; Lowry, Bullitt; Frey, Linda; Steinson, Barbara J.; King, Kay; Quinlivan, Mary E.; Harder, Peter J.; Armstrong, Thomas F.; et al. (Teaching History: A Journal of Methods, 2020)
J. M. MacKenzie. The Partition of Africa, 1880-1900. London and New York: Methuen, 1983. Pp. x, 48. Paper, $2.95. Review by Leslie C. Duly of Bemidji State University. C. Joseph Pusateri. A History of American Business. Arlington Heights, Illinois: Harlan Davidson, Inc., 1984. Pp. xii, 347. Cloth, $25.95; Paper, $15.95. Review by Paul H. Tedesco of Northeastern University. Russell F. Weigley. History of the United States Army. Enlarged edition. Bloomington: Indiana University Press, 1984. Pp. vi, 730. Paper, $10.95. Review by Calvin L. Christman of Cedar Valley College. Jonathan H. Turner, Royce Singleton, Jr., and David Musick. Oppression: A Socio-History of Black-White Relations in America. Chicago: Nelson-Hall, 1984. Cloth, $24.95; Paper, $11.95. Review by Thomas F. Armstrong of Georgia College. H. Warren Button and Eugene F. Provenzo, Jr. History of Education and Culture in America. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1983. Pp. xvii, 370. Cloth, $20.95. Review by Peter J. Harder. Vice President, Applied Economics, Junior Achievement Inc. David Stick. Roanoke Island: The Beginnings of English America. Chapel Hill and London: University of North Carolina Press, 1983. Pp. xiv, 266. Cloth, $14.95; Paper, $5.95. Review by Mary E. Quinlivan of the University of Texas of the Permian Basin. John B. Boles. Black Southerners 1619-1869. Lexington: The University Press of Kentucky, 1983. Pp. ix, 244. Cloth, $24.00; Paper, $9.00. Review by Kay King of Mountain View College. Elaine Tyler May. Great Expectations: Marriage and Divorce in Post-Victorian America. Chicago: University of Chicago Press, 1980. Pp. viii, 200. Cloth, $15.00; Paper, $6.95. Review by Barbara J. Steinson of DePauw University. Derek McKay and H. M. Scott. The Rise of the Great Powers, 1648-1815. London: Longman, 1983. Pp. 368. Paper, $13.95. Review by Linda Frey of the University of Montana. Jack S. Levy. War in the Modern Great Power System, 1495-1975. Lexington: The University Press of Kentucky, 1983. Pp. xiv, 215. Cloth, $24.00. Review by Bullitt Lowry of North Texas State University. Lionel Kochan and Richard Abraham. The Making of Modern Russia. Second Edition. New York: Penguin Books, 1983. Pp. 544. Paper, $7.95. Review by Pasquale E. Micciche of Fitchburg State College. D. C. B. Lieven. Russia and the Origins of the First World War. New York: St. Martin's Press, 1983. Pp. 213. Cloth, $25.00. Review by Joseph M. McCarthy of Suffolk University. John F. V. Kieger. France and the Origins of the First World War. New York: St. Martin's Press, 1983. Pp. vii, 201. Cloth, $25.00. Review by Robert B. Luehrs of Fort Hays State University. E. Bradford Burns. The Poverty of Progress: Latin Amerca in the Nineteenth Century. Berkeley: University of California Press, 1980. Pp. 185. Paper, $6.95. Review by Robert Fischer of the Southern Technical Institute. Anthony Seldon and Joanna Pappworth. By Word of Mouth: Elite Oral History. London and New York: Methuen, 1983. Pp. xi, 258. Cloth, $25.00; Paper, $12.95. Review by Jacob L. Susskind of the Pennsylvania State University, The Capitol Campus.